2018
DOI: 10.1371/journal.pntd.0006617
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 activation in cardiomyocytes contributes to the heart immune response to acute Trypanosoma cruzi infection with no effect on local parasite control

Abstract: Cardiomyopathy is the most serious consequence of Chagas disease, a neglected human disorder caused by Trypanosoma cruzi infection. Because T. cruzi parasites invade cardiomyocytes, we sought to investigate whether these cells recognize the parasite in vivo by receptors signaling through the MyD88 adaptor, which mediates the activation pathway of most Toll-like receptors (TLRs) and IL-1/IL-18 receptors, and influence the development of acute cardiac pathology. First, we showed that HL-1 cardiac muscle cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…It is reported that MyD88 plays a vital role in the development of heart disease 15,16 . So, we used Western blot assay to explore the expression of MyD88 in DMSO‐induced P19 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that MyD88 plays a vital role in the development of heart disease 15,16 . So, we used Western blot assay to explore the expression of MyD88 in DMSO‐induced P19 cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that MyD88 plays a vital role in the development of heart disease. 15 , 16 So, we used Western blot assay to explore the expression of MyD88 in DMSO‐induced P19 cells. Results showed that both mRNA and protein expression of MyD88 in p19 cells were down‐regulated at 0, 4, 6 and 10 days after DMSO stimulation (Figure 3A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…Além disto, em relação a estudos in vivo, o nosso grupo de pesquisa mostrou recentemente que os cardiomiócitos, principais vítimas na CCC, também contribuem in vivo à resposta imune cardíaca contra o parasito. Assim, no animal infectado pelo T. cruzi por um período de 10-30 dias foi observado que os cardiomiócitos são ativados através de receptores que utilizam o adaptador MyD88, sinalização que resulta em aumento significativo da produção local de quimiocinas e citocinas (Santana et al, 2018).…”
Section: Cardiomiopatia Chagásicaunclassified